2021
DOI: 10.3389/fimmu.2021.740562
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activation Of Aldehyde Dehydrogenase 2 Protects Against Heatstroke-Induced Acute Lung Injury by Modulating Oxidative Stress and Endothelial Dysfunction

Abstract: Heatstroke (HS) can cause acute lung injury (ALI). Heat stress induces inflammation and apoptosis via reactive oxygen species (ROS) and endogenous reactive aldehydes. Endothelial dysfunction also plays a crucial role in HS-induced ALI. Aldehyde dehydrogenase 2 (ALDH2) is a mitochondrial enzyme that detoxifies aldehydes such as 4-hydroxy-2-nonenal (4-HNE) protein adducts. A single point mutation in ALDH2 at E487K (ALDH2*2) intrinsically lowers the activity of ALDH2. Alda-1, an ALDH2 activator, attenuates the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 81 publications
(121 reference statements)
1
14
0
Order By: Relevance
“…Many investigations have demonstrated that Alda-1 protects against hyperoxia- or heatstroke-induced ALI. Alda-1 has lung-protective effects by inhibiting ROS generation and endothelial inflammation in the blood vessels [ 31 , 32 ]. Our work showed that mRNA and protein expressions of ALDH2 were considerably decreased in SAP-associated ALI rats' lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have demonstrated that Alda-1 protects against hyperoxia- or heatstroke-induced ALI. Alda-1 has lung-protective effects by inhibiting ROS generation and endothelial inflammation in the blood vessels [ 31 , 32 ]. Our work showed that mRNA and protein expressions of ALDH2 were considerably decreased in SAP-associated ALI rats' lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of sepsis-induced lung injury, Cao et al (17) demonstrated that Alda-1 treatment simultaneously reduced lung pyroptosis and ferroptosis and therefore alleviated its injury in mice. In the setting of heatstroke-induced lung injury, Tsai et al (18) demonstrated that Alda-1 treatment attenuated lung injury through the reduction of reactive oxygen species and toxic aldehydes, and the alleviation of vascular inflammation and endothelial dysfunction in in vitro and in vivo studies. In the case of regional lung IR injury, one study has demonstrated that Alda-1 treatment alleviated oxidative stress, inflammatory response, and apoptosis in human lung vascular endothelial cells and rats' lung tissues (9).…”
Section: Discussionmentioning
confidence: 99%
“…Other consequences of oxidative stress are oxidative modifications of cellular biomolecules. In such situation, ROS reacts with phospholipid PUFA, leading to lipid peroxidation and ultimately to the formation of reactive aldehydes such as 4-hydroxynonenal (4-HNE) and malondialdehyde (MDA) [36]. ROS may also indirectly modulate lipid metabolism, since lipid metabolizing enzymes are also over-activated under oxidative stress.…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Nevertheless, ROS can interact not only with transcription factors but also with other proteins, as well as with nucleic acids and especially lipids [46]. ROS react with phospholipids, in particular PUFA, which leads to lipid peroxidation with the generation of reactive aldehydes such as 4-hydroxynonenal (4-HNE) and malondialdehyde (MDA) [36].…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 99%